Menopause modified the association of blood pressure with osteoporosis among gender: a large-scale cross-sectional study - Jin, Haidong; Zhao, Hongfei; Jin, Sufan; Yi, Xianhong; Liu, Xiaotian; Wang, Chongjian; Zhang, Gongyuan; Pan, Jun (Frontiers in Public Health, 2024)
Purpose This study aimed to assess the potential association between blood pressure and osteoporosis in a rural population with limited resources. Existing evidence on this association is limited, particularly in such settings. Methods Data from 7,689 participants in the Henan Rural Cohort study were analyzed. Four blood pressure indicators [systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), and pulse pressure (PP)] were measured. The logistic regression model and restricted cubic spline plots were used to assess the relationship between blood pressure indicators and osteoporosis prevalence. Results Positive trends were noted between blood pressure indicators and osteoporosis prevalence in the entire group and women (Ptrend < 0.05 for SBP, MAP, and PP). Women with higher SBP and PP exhibited elevated odds of osteoporosis compared with those with the lowest SBP and PP (ORs ranging from 1.15 to 1.5 for SBP and 1.06 to 1.83 for PP). No such associations were found in men. These relationships were only evident in postmenopausal women. Dose–response analysis confirmed these findings. Excluding participants taking hypertension medication did not alter the results. Conclusion In resource-limited settings, higher SBP and PP are associated with the increased prevalence of osteoporosis in women, potentially influenced by menopause-related factors. This indicates that potential gender-based differences and social inequalities may affect bone health. Clinical trial registration The Henan Rural Cohort Study has been registered at the Chinese Clinical Trial Register (Registration number: ChiCTR-OOC-15006699) http://www.chictr.org.cn/showproj.aspx?proj=11375.